Fatal canine parvovirus type 2a and 2c infections in wild Chinese pangolins (Manis pentadactyla) in southern China. Issue 6 (22nd September 2022) - Lina, Zhang; Kai, Wang; Fuyu, An; Dongliang, Zhang; Hailing, Zhang; Xuelin, Xu; Ce, Guo; Hongmei, Yan; Yingjie, Kuang; Zhidong, Zhang; Rongguang, Lu; Yan, Hua
Abstract: The Chinese pangolin ( Manis pentadactyla ) is a critically endangered scale‐covered mammal belonging to the order Pholidota. Wild pangolins are notably susceptible to pathogen infection and are typically characterized by impoverished health. However, little is currently known regarding the viruses prevalent among pangolins. In this study, we report the detection of two subtypes of canine parvovirus type 2 (CPV‐2), namely CPV‐2a and CPV‐2c, both of which caused severe diarrheal disease in two post‐rescue pangolins with fatal consequences. As in CPV‐2‐infected dogs, intensive lesion of the mucosal layer of the small intestines is a prominent feature in infected pangolins. Moreover, the immunochemistry results demonstrated that CPV‐2 antigens were distributed in the crypts of small intestine. Additionally, typical parvovirus‐associated CPV‐2 were detected after four passages in F81 cells, and typical parvovirus‐like particles, approximately 20 nm in diameter, were observed in the cell supernatants. Phylogenetic analysis revealed that the VP2 viral protein sequences (GenBank accession number OP208805) isolated from one pangolin (termed P1) were classified as CPV‐2c, with 99.8% identity to a CPV‐2c strain (MN832850) isolated from a Taiwanese pangolin found in Taiwan Province. In contrast, VP2 sequences (#OP208806) obtained from the second pangolin (P2) were classified as CPV‐2a, with 99.8% identity to a CPV‐2a strain (KY386858) isolated from southern China. In this study, we thus confirmed the infection of pangolins with CPV‐2c in mainland China and demonstrated that CPV‐2a also can infect pangolins. Based on these findings, we recommend that further investigations should be conducted to establish the interspecies transmission of these viruses among wild pangolins, wild carnivores, and stray dogs.